Compliance with Business Permits and Licensing System Requirements: Effects on Business Performance and Satisfaction Among MSMEs - Niño, Ace Gerome; Gentoral, Francisco (Journal of Interdisciplinary Perspectives, 2024)
This study investigated the relationships and differences among compliance levels, business performance, and satisfaction with the Business Permits and Licensing System (BPLS) requirements among 390 Micro, Small, and Medium Enterprises (MSMEs) in Iloilo City, Philippines. Using a descriptive, quantitative, and correlational design, the study sampled MSMEs from various industry sectors using the Input-Process-Output (IPO) model. Results show that MSMEs, particularly in sectors C and D, reported high compliance with BPLS requirements. It implies strong adherence to the requirement, suggesting effective engagement with the regulatory system. They also rated their business performance, including changes in gross sales, sales growth, capitalization, capital turnover, employee numbers, and overall satisfaction, as very good to excellent. It suggests they are experiencing strong financial performance, indicating a positive economic impact. High satisfaction with BPLS was also noted, which implies that the system is easy and efficient, leading to improved compliance and more favorable business conditions. T-tests and ANOVA revealed differences and similarities in compliance, business performance, and satisfaction across different business types and sectors, suggesting that these factors are affected by specific attributes of each business group. Pearson's correlation analysis indicated a negligible relationship between compliance and business performance, a very strong positive relationship between compliance and satisfaction, and a weak positive relationship between business performance and satisfaction. It implies that compliance significantly enhances satisfaction and has little impact on business performance. The study's recommendations, such as fully implementing an electronic BPLS and customer feedback system as part of the EODB law and including additional financial indicators in the unified application form, are of utmost importance. Future research should extend the analysis to other cities and local governments in the Visayas to further explore the linkage between compliance, business performance, and satisfaction.